Acronim Indonesian Language In Adolescents - Fitrianingsih, Rina Ayu; Amilia, Fitri; Kamila, Devi Faricha Rahman; Sari, Febriani Permata Ratna (PBSI, FKIP UNISSULA, Semarang, 2023)
This study describe the use of Indonesian acronyms among adolescents. This research is based on the phenomenon of the use of acronyms by teenagers on social media. Data was collected by looking for acronyms in the comments column, documenting them, classifying them, and finding their distinguishing features. The results of the analysis are presented in a descriptive and explanatory. Based on the results, the use of acronyms is divided into regular patterns and irregular patterns. Regular patterns are found in acronyms with two syllables. The pattern is abbreviation of the first syllable in the first word and the second word; abbreviation of the first syllable in the first word and the second syllable in the second word. The patterns varies is an addition of a phoneme before the first or second syllable. The addition of these phonemes is regular, namely taking phonemes before or after each abbreviated syllable. The regularity of this pattern is in line with the phonotactic conventions in Indonesian. Phonomatic patterns and rules in acronyms are in line with the ease of pronunciation and similarities with Indonesian word patterns. Based on these findings, Indonesian acronyms will continue to develop according to the dynamics of language use.